Collective photon emission of two correlated atoms in free space - Richter, Stefan; Wolf, Sebastian; von Zanthier, Joachim; Schmidt-Kaler, Ferdinand (Physical Review Research, 2023)
By preparing two distant emitters in entangled Dicke states via detection of a single photon, the subsequent spatiotemporal photon emission is investigated. Depending on the parity of the established quantum state, emission patterns for the second scattered photon are observed featuring spatial superradiance as well as subradiance. We employ ultrafast single-photon resolving cameras with high spatial resolution disclosing the spatiotemporal emission characteristics. By recording the first photon in one direction and the second photon in another, revealing the spatial two-photon cross-correlation function g(2)(r1, r2), we characterize the collective spontaneous emission behavior of two ions in free space. We explain the observed contrast of g(2)(r1, r2) considering independently derived experimental parameters. Our results show how the detection of a single photon can profoundly modify the collective spontaneous emission dynamics of an atomic ensemble.
CRIS-Team WoS Importer:2023-04-07